Artemesiaannua L. Silver Nanoparticles Exhibit Anticancer Activity by ROS mediated apoptosis in MDA-MB-231 Cells - Renugadevi Karthikeyan1 , Julius Amaldas2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim of this study was to investigate the growth inhibitory effect of Artemesisannua L. silver nanoparticles(A.annuaAgNPS) on human triple negative breast cancer tumor cell line MDA-MB-231. Cells werecultured and treated with A.annua water extract and A.annuaAgNPS to determine the half inhibitoryconcentration (IC50). Oxidative stress was determined using lipid peroxidation (LPO), ROS generation andby determining the levels of antioxidants, superoxide dismutase (SOD) and reduced glutathione (GSH).Further, the mechanism of apoptotic induction was assessed by DNA fragmentation analyses. We observedthat A.annuaAgNPS significantly caused growth inhibition by increasing levels of LPO and ROS, in a dosedependent manner with reduced level of endogenous antioxidant enzymes. Increased shear in genomic DNAfrom MDA MB231 cells treated with A.annuaAgNPS shows apoptosis to be the cause of cell cell death. Weconclude that A.annuaAgNPS can be useed as a therapeutic agent against breast cancer.